2012
DOI: 10.1074/jbc.m112.400135
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Cell Nuclear Antigen (PCNA)-binding Protein C1orf124 Is a Regulator of Translesion Synthesis

Abstract: Background: Translesion synthesis involves proliferating cell nuclear antigen (PCNA) monoubiquitination and polymerase switching. Results: C1orf124 is required for cell survival following UV damage. It binds to monoubiquitinated PCNA and participates in polymerase switching. Conclusion: C1orf124 serves as a central platform that facilitates translesion synthesis. Significance: This study provides a mechanism for translesion synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 40 publications
(48 reference statements)
7
122
0
3
Order By: Relevance
“…We mapped the DNA-binding box in the SPARTAN sequence and generated a point mutant SPARTAN that was partially defective in DNA binding. Previously, we and others described that the ubiquitylation of PCNA regulates the subnuclear targeting of SPARTAN [24][25][26]28]. We demonstrate that the DNA binding of SPARTAN is not essential for its intranuclear distribution.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations
“…We mapped the DNA-binding box in the SPARTAN sequence and generated a point mutant SPARTAN that was partially defective in DNA binding. Previously, we and others described that the ubiquitylation of PCNA regulates the subnuclear targeting of SPARTAN [24][25][26]28]. We demonstrate that the DNA binding of SPARTAN is not essential for its intranuclear distribution.…”
Section: Resultsmentioning
confidence: 44%
“…Previously, we and others have shown that SPARTAN plays a critical role in the regulation of targeting Polη, in which the binding of Ub-PCNA via its PIP and UBZ domains is very important [26][27][28]. In parallel, it has been proposed that -besides Ub-PCNA binding -another targeting mechanism could be present by which SPARTAN regulates damage bypass [25,26,32]. Therefore, we tested how the DNA binding of SPARTAN affects Polη foci formation.…”
Section: Dna Binding Is Essential For the Dna Repair Function Of Spartanmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation may trigger recombination-dependent repair, e.g., by break-induced replication (BIR), though with the risk of genomic rearrangements (GCRs). the precise role of Dvc1/Spartan remains highly controversial despite recent efforts (Centore et al, 2012;Davis et al, 2012;Ghosal et al, 2012;Juhasz et al, 2012;Kim et al, 2013;Machida et al, 2012;Mosbech et al, 2012;Vaz et al, 2013). Some studies suggested that Dvc1/Spartan plays a role in conjunction with Cdc48/p97 in removal of Polh from chromatin, but the significance of Dvc1/Spartan's protease domain remained unsolved (Davis et al, 2012;Mosbech et al, 2012).…”
Section: Discussionmentioning
confidence: 99%